Material Realities and Ideological Paradigms in Afterlives: A Marxist Reimagining - Pokharel, Bishnu Prasad; Thapa, Mumaya (NPRC Journal of Multidisciplinary Research, 2025)
Background: Abdulrazak Gurnah’s Afterlives (2020) explores the aftermath of German colonial rule in an unnamed coastal town in East Africa, shedding light on how imperial economic agendas shaped and disrupted local lives. The novel critiques the far-reaching consequences of German colonial capitalism by portraying how systems of education, law, culture, and ideology were weaponized to establish a superstructure that justified and sustained material exploitation. Methods: This study adopts Karl Marx’s and Raymond Williams’s theory of base and superstructure to analyze both the tangible and intangible dimensions of colonial domination. It investigates how material exploitation operates through forced labor, military conscription, and social hierarchies, while ideological control is exercised through educational indoctrination, the promise of "civilization," and religious authority. Character trajectories are used as lenses to examine these intersecting modes of control. Results: The characters—Ilyas, Afiya, Khalifa, and Hamza—serve as case studies of individuals caught within the machinery of empire. Despite appearing to benefit from German rule through employment or association, they suffered emotional detachment, cultural dislocation, and internalized oppression. The colonial system maintains power not merely through force but through ideological instruments that obscure the nature of exploitation, leading to a distorted perception of material progress. Conclusion: The novel dramatizes a fundamental tension between the economic base and the ideological superstructure. It reveals how colonial institutions outlast political occupation, continuing to affect the thoughts, identities, and relationships of formerly colonized subjects. The narrative thus critiques not only colonial violence but also the lingering ideological residues that inhibit true liberation. Novelty: This study argues that the German colonial project in East Africa marks a period of deep psychological and socio-political trauma, where material gains such as education and employment failed to liberate the colonized. Instead, they reinforced dependence and obedience. The novel portrays a gradual awakening among the characters, suggesting that freedom only becomes possible through the decolonization of material conditions and internalized beliefs. This dual insight into structural and psychological liberation distinguishes the novel and enriches postcolonial discourse.